2018
DOI: 10.7748/ns.2018.e10829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of non-healing wounds

Abstract: Chronic wounds are defined as those that have failed to heal after three months. There are various intrinsic and extrinsic factors that may result in the development of chronic wounds, including comorbidities such as diabetes mellitus and venous insufficiency, and lifestyle factors such as obesity, alcohol consumption and smoking. Chronic wounds represent a significant burden on healthcare resources and can have a negative effect on patients' quality of life. This article discusses the assessment and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Chronic or non-healing wounds continue to be a public health issue because their prevalence is rising due to population aging, increased longevity, and diseases, such as arterial insufficiency, venous insufficiency, and diabetes . The field of nanotechnology can provide new approaches to regenerative medicine .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic or non-healing wounds continue to be a public health issue because their prevalence is rising due to population aging, increased longevity, and diseases, such as arterial insufficiency, venous insufficiency, and diabetes . The field of nanotechnology can provide new approaches to regenerative medicine .…”
Section: Introductionmentioning
confidence: 99%
“…5,[18][19][20][23][24][25][26][27][31][32] This action is related to the mechanisms of the proliferative phase of cicatrization, which corresponds to the formation of the granulation tissue and the new vessels of the cell matrix. 33 It is inferred that there was also positive evidence related to re-epithelialization of chronic wounds and the acceleration of healing, as well as decrease of pain during treatment. 33 It is observed that the action of the laser has proved effective when associated with other therapies for skin and tissue injuries.…”
Section: Discussionmentioning
confidence: 99%
“…33 It is inferred that there was also positive evidence related to re-epithelialization of chronic wounds and the acceleration of healing, as well as decrease of pain during treatment. 33 It is observed that the action of the laser has proved effective when associated with other therapies for skin and tissue injuries. In a retrospective study with patients with Achilles tendon injury, it is suggested that the laser associated with topical hyperbaric therapy is an alternative treatment with positive effects on keratinocyte proliferation, fibroblast organization and anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 99%
“…Luka kronis didefinisikan sebagai luka yang gagal sembuh setelah tiga bulan. Ada berbagai faktor instrinsik dan ekstrinsik yang dapat menyebabkan berkembangnya luka kronis termasuk penyakit penyerta seperti diabetes mellitus, insufisiensi vena, faktor gaya hidup seperti obesitas, konsumsi alkohol dan merokok (Tapiwa, 2018). Madu merupakan salah satu terapi komplementer yang dapat digunakan sebagai terapi topikal dalam perawatan luka.…”
Section: Pembahasanunclassified